Changes in P2Y Purinergic Receptor Expression in the Ciliary Body in a Murine Model of Glaucoma - Fonseca, Begoña; Martínez-Águila, Alejandro; Pérez de Lara, María J.; Miras-Portugal, Maria Teresa; Gómez-Villafuertes, Rosa; Pintor, Jesús (Frontiers in Pharmacology, 2017)
Glaucoma is a neuropathology, often accompanied by an elevated intraocular pressure (IOP), which can lead to blindness. Since DBA/2J mice develop glaucoma, several studies of the physiopathology of glaucoma have been reported in this animal model. It is also known that purinergic receptors are involved in the pathology of glaucoma by controlling aqueous humour production and drainage and therefore controlling IOP. There are no studies on purinergic receptors in the DBA/2J model of glaucoma and their relation to the development of the pathology, so the aim of this study was to make an approach to the purinergic mechanisms involved in glaucoma. All the experiments were performed using DBA/2J and C57BL/6J mice and investigating P2Y1, P2Y2, and P2Y6 receptors. IOP measurements were made with a non-invasive rebound tonometer, and animals were instilled with diadenosine tetraphosphate (Ap4A) and the corresponding purinergic antagonists in order to see their effects on IOP. mRNA expression for P2Y1, P2Y2, and P2Y6 purinergic receptors was carried out by q-PCR. Additionally, P2Y-receptor expression was performed by immunohistochemical techniques carried out on the ciliary processes. The results showed that IOP decreases when Ap4A was instilled and that the expressions of the analyzed purinergic receptors were stable throughout all the ages under study in the C57BL/6J mice (control mice). On the other hand, there were significant changes in the purinergic receptor expression in DBA/2J suggesting that elevated IOP in these animals could be related to an increase of P2Y2 expression and a decrease in P2Y1 receptors.